2020
DOI: 10.1103/physrevlett.125.206402
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Topological Edge States in Non-Hermitian Piezophononic Media

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…By controlling the non-reciprocal coupling between arbitrary two sites, more complex unconventional topological windings can be achieved in the present acoustic platform. As the NHSE is a manifestation of the breakdown of the conventional bulk-boundary correspondence, it will be interesting to investigate the generalization of bulkboundary correspondence and generalized Brillouin zones in non-Hermitian topological acoustics 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By controlling the non-reciprocal coupling between arbitrary two sites, more complex unconventional topological windings can be achieved in the present acoustic platform. As the NHSE is a manifestation of the breakdown of the conventional bulk-boundary correspondence, it will be interesting to investigate the generalization of bulkboundary correspondence and generalized Brillouin zones in non-Hermitian topological acoustics 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Introducing a boundary will only lead to boundary states, but will not change any bulk property, including the band topology, as considered universally true for all Hermitian, or energyconservative, systems. However, the recently discovered NHSE has shown that non-Hermiticity, originating from loss/gain or non-reciprocity, can cause all the bulk eigenstates to collapse towards the introduced boundary [3][4][5][6][7][8][9][10][11][12][13][14][15] . The complete collapse of bulk bands in NHSE has posed a challenge to the bulk-boundary correspondence 3 -a fundamental principle of topological physics-which states that the band topology derived from the bulk dictates the topological phenomena at the boundary.…”
mentioning
confidence: 99%
“…Non-Hermitian topological physics [1][2][3][4][5] is attracting a considerable interest since the past few years, with a wealth of novel phenomena which do not have any counterpart in corresponding Hermitian topological systems (see and references therein). The ability to experimentally implement and control non-Hermiticity using synthetic lattices has been demonstrated using different physical platforms ranging from photonic [35,38,39,47,48], acoustic [14,45] and micro mechanical [33,34] systems to topolectrical circuits [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…It works, for example, for the aforementioned Chern insulator and Z 2 topological insulator with manifestation as gapless chiral and helical edge states, respectively. However, this relationship turns out to be faced with the demanding for modification at least by two cases: non-Hermitian [26][27][28][29][30] and higher-order topo-logical systems [31][32][33][34][35][36]. In the former case, one-by-one situations need corresponding generalizations, and in the latter case there are simply no gapless boundary states at all on boundaries with unit-lower dimensions.…”
mentioning
confidence: 99%